Development and regional characteristics of the Hungarian information and communication sector (ICT) - Gábor Nagy; Imre Kanalas (Netcom, 2009)
The rapid development of IC technologies and in parallel the increasing demand for more information and knowledge from the actors of economy, institutions and members of society created the ICT-sector into the core of “new economy” and information society. This process got an important role in the major research topics in economic and social geography, thanks to the high innovation capacity of the sector, the new forms of organizing economic activities and the discussed spatial and social effects of the development. The rising ICT sector and new elements of information society implied a special interest not only from basic research, but even applied research areas, for example the emerging role of ICTs in regional development and regional policies and some sectoral policies (economy, education, health etc.). This process had a special role in the former COMECON area. The info-intensive activities had a crucial role in building up a new, market-led model of economy in the transition period. The new forms of communication offer to re-organize the personal connections, the local societies and created new “spaces and places” for new communities. The double modernisation effect of ICTs in converging countries in the period of transition (1989/1990 – 2004) had a serious impact on spatial processes. In our paper we concentrate on the role of ICTs in transforming Hungarian economy, increasing the competitiveness of the country. We try to describe the spatial structure of the sector and its part in forming the new regional structure of the country.